Gastric Microbiota beyond H. pylori: An Emerging Critical Character in Gastric Carcinogenesis - Jun Wen (MDPI AG, 2021)
Gastric cancer (GC) is one of the global leading causes of cancer death. The association between Helicobacter pylori, which is a predominant risk factor for GC, with GC development has been well-studied. Recently, accumulating evidence has demonstrated the presence of a large population of microorganisms other than H. pylori in the human stomach. Existing sequencing studies have revealed microbial compositional and functional alterations in patients with GC and highlighted a progressive shift in the gastric microbiota in gastric carcinogenesis with marked enrichments of oral or intestinal commensals. Moreover, using a combination of gastric bacterial signatures, GC patients could be significantly distinguished from patients with gastritis. These findings, therefore, emphasize the importance of a collective microbial community in gastric carcinogenesis. Here, we provide an overview of non-H. pylori gastric microbes in gastric carcinogenesis. The molecular mechanisms of gastric microbes-related carcinogenesis and potential clinical applications of gastric microbiota as biomarkers of GC are also explored.